(untitled) (Journal of the College of Basic Education, 2026)
Given the central importance of Medina, a city that enjoys a high status throughout Saudi Arabia and is beloved by all Muslims, there was a pressing need for reform and modernization projects in the area of ​​the Two Holy Mosques (Mecca and Medina). This included improving traffic flow directly to the northern roads, lighting, irrigation, and agricultural projects, thereby easing the burden on pilgrims traveling to the Holy Mosque. Prior to the discovery of commercial oil, the prevailing culture of nomadic life, backwardness, and migration characterized investment in Saudi Arabia. In 1938, there were strong calls for Islamic reform and modernization projects in Mecca, Medina, and their surrounding areas. Egypt and its experts played a significant and active role in laying the foundations for this progress and the beginnings of reform in the Two Holy Mosques. This included constructing and repairing roads, providing potable water, cultivating the areas around the Two Holy Mosques, and illuminating them, in addition to other projects that required adequate resources.